Assessment of Compliance of Medical Tourists Host Hospitals in Shiraz with Global Criteria - Omid Sadeghkhani; Sara Shahbazi; Hamid Talebianpour; Parisa Bikineh; Peivand Bastani (Kerman University of Medical Sciences, 2019)
Assessment of Compliance of Medical Tourists Host Hospitals in Shiraz with Global Criteria   Sadeghkhani Omid1, Shahbazi Sara2, Talebianpour Hamid3, Bikineh Parisa4, Bastani Peivand5*   1. MSc Student in Healthcare Management, Student Research Committee, School of Management and Medical Informatics, Shiraz University of Medical Sciences, Shiraz, Iran 2. MSc Student in Healthcare Management, School of Public Health, Department of Management Sciences and Economics, Tehran University of Medical Sciences, Tehran, Iran 3. Ph.D. Student in Health Economy, School of Public Health, Department of Management Sciences and Economics, Tehran University of Medical Sciences, Tehran, Iran 4. MSc Student in Healthcare Management, Student Research Committee, Shiraz University of Medical Sciences, Shiraz, Iran 5. Associate Professor, Health Human Resources Research Center, Shiraz University of Medical Sciences, Shiraz, Iran *Correspondence: Health Care Management and Medical Informatics School, Almas Building, Alley 29, Ghasrodasht Ave., Shiraz, Iran. Tel: 00987132340039                                               Email: bastanip@sums.ac.ir Abstract: Background & Objectives: Medical tourism as a growing industry contributes to GDP growth and employment, and improves infrastructure in the country. Hospitals compliance with global criteria would undoubtedly increase the quality of therapeutic services for medical tourists. Hence, this study was conducted to evaluate the compliance of hospitals of Shiraz hosting medical tourists with global criteria. Methods: This descriptive-analytical cross-sectional study was conducted in six hospitals with medical tourism units in Shiraz in 2018. Data were collected through a researcher-made checklist containing 48 questions with 6 dimensions. Data were analyzed using Spearman's correlation coefficient by SPSS version 22. Results: The examined hospitals were compliant with global criteria in terms of infrastructure facilities, quality of health services, and human resources management. In terms of accreditation and welfare dimensions, 3 hospitals matched with global criteria. However, none of the hospitals matched with global criteria of medical tourism services dimension. There was a significant correlation between the number of active beds and welfare services (P=0.00). Conclusion: According to the relative compliance of Shiraz hospitals with global criteria for admission of medical tourists, it is necessary to pay attention to welfare and medical tourism services in order to develop medical tourism in Shiraz.    Keywords: Medical tourism, International patient, Private hospital, Global criteria   Citation: Sadeghkhani O, Shahbazi S, Talebianpour H, Bikineh P, Bastani P. Assessment of Compliance of Medical Tourists Host Hospitals in Shiraz with Global Criteria. Journal of Health Based Research 2019; 5(1): 29-43. [In Persian]